Evaluating wind technicians' performance on safety-critical rescue steps. Issue 1 (20th July 2018) - Lawani, Kenneth; Hare, Billy; Cameron, Iain
Abstract : This paper reports the results of an analysis on the performance levels of wind technicians at 1 month and 3 months on safety-critical steps using situational judgement tests (SJTs) and job knowledge tests (JKTs) to assess their emergency rescue and evacuation proficiency. The research design is a repeat-measures study (longitudinal), using SJTs and JKTs to assess job-specific knowledge and job-related situations. It measured procedural knowledge in addition to aspects of declarative knowledge and fluid abilities, and this was considered as a good predictor of performance for wind technicians. The results indicate that rescue and evacuation skills decay within 1 month and 3 months after wind turbine rescue and evacuation training with 47 and 20% of technicians experiencing such decay in their skills and knowledge. These findings have practical implications for activities involving rescue and evacuation of workers – for example, crane driver rescue. The implementation of SJTs and JKTs indicates that skill decay takes place within the first 4 weeks after acquisition. Likewise, job knowledge is more resistant to decay compared with skill tasks over the 3 months' retention time frame for both refresher and new wind technicians.